2021
DOI: 10.1186/s12885-021-08881-7
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment patterns and effectiveness of patients with multiple myeloma initiating Daratumumab across different lines of therapy: a real-world chart review study

Abstract: Background Daratumumab, a CD38 monoclonal antibody, has demonstrated efficacy as monotherapy and combination therapy across several indications, both among newly-diagnosed and refractory patients with multiple myeloma (MM). However, there is limited evidence on treatment patterns and effectiveness of daratumumab in the real-world setting, particularly in first line (1 L). This study aimed to describe real-world treatment patterns and clinical outcomes among patients initiating daratumumab acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…While clinical trials demonstrate impressive benefit of darabased therapies, possible discordance with real-world practice might exist, as many patients in the real world are known to be ineligible for clinical trials. 22,23 A few small real-world multicentre studies specifically focusing on dara have been published, confirming the promising activity noted in clinical trials [23][24][25][26][27] [28][29][30][31] There remains a paucity of studies evaluating the outcomes of dara-containing regimens in larger realworld cohorts. Our study aimed to evaluate the impact of these regimens and to benchmark outcomes that may identify gaps that can be targeted for future optimization.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…While clinical trials demonstrate impressive benefit of darabased therapies, possible discordance with real-world practice might exist, as many patients in the real world are known to be ineligible for clinical trials. 22,23 A few small real-world multicentre studies specifically focusing on dara have been published, confirming the promising activity noted in clinical trials [23][24][25][26][27] [28][29][30][31] There remains a paucity of studies evaluating the outcomes of dara-containing regimens in larger realworld cohorts. Our study aimed to evaluate the impact of these regimens and to benchmark outcomes that may identify gaps that can be targeted for future optimization.…”
mentioning
confidence: 75%
“…While clinical trials demonstrate impressive benefit of dara‐based therapies, possible discordance with real‐world practice might exist, as many patients in the real world are known to be ineligible for clinical trials 22,23 . A few small real‐world multicentre studies specifically focusing on dara have been published, confirming the promising activity noted in clinical trials 23‐27 (Atrash et al, 2021; Harvanová et al, 2021; Maouche et al, 2021; Szabo et al, 2021) 28‐31 . There remains a paucity of studies evaluating the outcomes of dara‐containing regimens in larger real‐world cohorts.…”
mentioning
confidence: 99%
“…Daratumumab has demonstrated efficacy as monotherapy and combination therapy across several indications, both among newly diagnosed and refractory patients with MM. Daratumumab-based regimens are an effective treatment option across all lines of therapy, with highest response rate in first-line [55]. Daratumumab triplet regimen (DRd) has been shown to be superior to other triplet regimens for the treatment of RR-MM, and daratumumab monotherapy has been shown to be more effective than either single agent in heavily pretreated MM patients, suggesting that daratumumab is effective in the treatment of RR-MM [56].…”
Section: Treatment Of Relapsed and Refractory MMmentioning
confidence: 99%
“…Author details 1 Levine Cancer Institute, Charlotte, NC, USA. 2 Analysis Group, Inc, 1190 avenue des Canadiens-de-Montréal, Deloitte Tower, Suite 1500, Montreal, QC H3B 0G7, Canada.…”
Section: • Rapid Publication On Acceptancementioning
confidence: 99%
“…Correction to: BMC Cancer 21, 1207 (2021) https://doi.org/10.1186/s12885-021-08881-7 Following publication of the original article [1], it was identified that due to typesetting mistakes, an unfinalized version of the article were published. The following changes have been implemented.…”
mentioning
confidence: 99%